Uso da argila silicatada como fonte de silício na produção de sementes de cereais - Lima, Bento Alvenir Dornelles de (2010)
Rio Grande do Sul, which produces a variety of crops being the important cereal rice sown in spring / summer and wheat and barley with high potential for cultivation in the autumn / winter. The state accounts for the increased production of rice (Oryza sativa L.) in Brazil, with an acreage of about one million hectares per year. The wheat (Triticum aestivum L.) is intended for grain production, which are processed into flour for the bakery and pasta, the culture of barley (Hordeum vulgare L.) is intended for grain production, which are transformed malt in the brewing industry. The use of silicon has the potential to reduce the use of agrochemicals and increase productivity through balanced nutrition and physiologically more efficient. Silicate clay is a whitish powder contains 77.9% SiO2 at pH 5.5. This study aimed to evaluate the physiological quality, seed yield in the field of grain treated with silicate clay as a source of silicon. We used two foliar treatments with four applications and on the ground with three doses were: T1 360 kg ha ˉ ¹, T2 720 kg ha ˉ ¹ in four foliar applications on vegetative stages V4, V9 and reproductive R2 and R6 and at sowing T3 360 kg ha ˉ ¹, 720 kg ha T4 and T5 ˉ ¹ zero. We conclude that the use of silicate clay had no interference in the physiological quality and productivity of rice seeds and the response was different for genotypes of wheat and barley.